Impact of Procalcitonin Guidance on the Management of Adults Hospitalized with Pneumonia. (4th October 2017) - Walsh, Thomas; DiSilvio, Briana; Hammer, Crystal; Beg, Moeezullah; Vishwanathan, Swati; Speredelozzi, Daniel; Moffa, Matthew; Hu, Kurt; Abdulmassih, Rasha; Makadia, Jina; Sandhu, Rikinder; Naddour, Mouhib; et al.
Abstract: Background: Community-acquired pneumonia and healthcare-associated pneumonia are often treated with prolonged antibiotic therapy. Procalcitonin (PCT) has effectively and safely reduced antibiotic use for pneumonia in controlled studies. However, limited data exist regarding PCT guidance in real-world settings for management of pneumonia. Methods: A retrospective, preintervention/postintervention quality improvement study was conducted to compare management for patients admitted with pneumonia before and after implementation of PCT guidance at two teaching hospitals in Pittsburgh, Pennsylvania. The preintervention period was March 1, 2014 through October 31, 2014, and the post-intervention period was March, 1 2015 through October 31, 2015. Results: A total of 152 and 232 patients were included in the preintervention and postintervention cohorts, respectively. When compared with the preintervention group, the mean duration of therapy decreased (9.9 vs. 6.1 days; P < 0.001). More patients received an appropriate duration of 7 days or less (26.9% vs. 66.4%; P < 0.001). Additionally, mean hospital length of stay decreased in the postintervention group (4.9 vs. 3.5 days; P = 0.006). Pneumonia-related 30-day readmission rates (7.2% vs. 4.3%; P = 0.99) were unaffected. In the postintervention group, patients with PCT levels < 0.25 µg/l received shorter mean duration of therapy compared with patients with levels >0.25 µg/l (8.0 vs. 4.6 days; P < 0.001) as well as reduced hospital length of stay (3.9 vs. 3.2 days; P = 0.02). Conclusion: In this real-world practice study, PCT guidance led to shorter durations of total antibiotic therapy and abridged inpatient length of stay without affecting hospital re-admissions. Disclosures: All authors: No reported disclosures.